2015
DOI: 10.1021/acs.iecr.5b00518
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Stability of Biosorbents for Metal-Ion Adsorption

Abstract: Biosorbents have demonstrated great potential in the treatment of metal-containing wastewater. However, one of the bottleneck issues of using biosorbents is that amounts of organic carbon release from biosorbents into water. This seriously limits the application of biosorption technology in treating wastewater. In this work, a novel methodology was developed to greatly reduce the organic carbon release and enhance the stability of biosorbents by using barley straw as the model biosorbent material and nickel as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Modeling approach based on the Dubinin−Polanyi model has been employed for water adsorption equilibrium on carbon nanomaterials, 41 modified rice husk, 42 corn meal, 43 and canola meal. 25 This model has been found to give the most reasonable representation of the equilibrium isotherm data in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling approach based on the Dubinin−Polanyi model has been employed for water adsorption equilibrium on carbon nanomaterials, 41 modified rice husk, 42 corn meal, 43 and canola meal. 25 This model has been found to give the most reasonable representation of the equilibrium isotherm data in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, adsorption is generally preferred to address heavy metal ion pollution due to its simple operation and potential recovery and reuse of metals. In this context, a vast variety of adsorbents including activated carbons, clay material, zeolites, and biosorbents have been developed to remove heavy metal ions from various industrial effluents in past years. …”
Section: Introductionmentioning
confidence: 99%
“…Functionalisation of nanobiomaterial was reported by Zhang et al [30] who used layered double hydroxide as a functionalised reagent for the removal of anions. Ou et al [31] reported functionalisation of biomaterial with sodium alginate and poly(vinyl alcohol) for enhancement of the stability of the biosorbent (Barley straw) and explored its sorption efficiency for cationic metals. Similarly, Zargoosh et al [32] reported functionalised nanobiomaterial with thiosalicylhydrazide for the removal of cationic metals.…”
Section: Introductionmentioning
confidence: 99%